Integration and Interconnection of Islamic Religious Education in the Perspective of Self-Environment Relations for the Development of Education Based on Islamic Values - Darsimon, Darsimon; Aminulla, Muhammad; Rivai, Muhammad; Firman, Firman; Amir, Amri; Kasmawati, Kasmawati; Jasriani, Jasriani; Lestari, Laili; Malli, Rusli (International Journal on Advanced Science, Education, and Religion, 2025)
This article explores the concept of self-environment relationship from the perspective of Islamic education, emphasizing the importance of a holistic approach in preserving the environment. This study aims to analyze how Islamic education can be integrated with ecological values ​​to create collective awareness of environmental preservation. Based on the literature review, Islam teaches human responsibility as a caliph to maintain the balance of the ecosystem. This article uses a literature analysis method with an interdisciplinary approach, including the interpretation of the verses of the Qur'an, Islamic environmental ethics, and the application of these values ​​in the education system. The results of the study indicate that education based on Islamic values ​​can increase environmental awareness and provide solutions to ecological damage. This study emphasizes the importance of integrating Islamic religious education with environmental issues as a solution-oriented and sustainable strategy.